Penggunaan Diksi dalam Menulis Teks Puisi Siswa Kelas VIII SMP Negeri 27 Makassar - Chyntya, Prety; Usman, Usman; Baharman, Baharman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the use of diction in writing poetry texts by eighth grade students of SMP Negeri 27 Makassar. This study uses qualitative descriptive. The focus of this study is to analyze data on poetry texts created by students to describe the use of diction used in their poetry. The data in this study is diction in students' poetry texts. The data sources for this study were taken from students' poetry texts. Data collection techniques were carried out through observation, assignments, and documentation. Data analysis techniques applied in this study were reduction, data presentation, and drawing conclusions. The results showed that the most dominant types of diction used were connotative diction and abstract words. Meanwhile, types of diction such as synonyms, antonyms, slang words, jargon words, and slang were almost never found. This finding indicates that students' ability to choose diction is still limited and tends towards general and emotional diction. Therefore, this study recommends the need for learning that is more focused on the variation and application of diction in writing poetry so that students are able to express their ideas and feelings more richly and creatively.